Socio-Ecological Effect of Transition Landscape Dynamics from Agroforests to Monoculture Plantation in Upper Citarum Watershed - Nugraha, Luthfan Meilana; Hakim, Lukmanul; Abdoellah, Oekan Soekotjo; Darmawan, Arief; Winarno, Bondan (Jurnal Sylva Lestari, 2024)
Agroforests in many tropical countries have long been acknowledged as substantially necessary to contribute to biodiversity conservation and community livelihood. The importance of agroforest biodiversification is now overlooked and replaced by a simplified structure due to the impact of agricultural commercialization. Land use changes have occurred in the Upper Citarum Watershed over time, converting traditional agroforests into monoculture plantations at the expense of their socio-ecological function. This paper aimed to analyze land use change dynamics and the effect of biodiversity loss on the socio-economy aspect of the rural agricultural landscape in the Upper Citarum Watershed. We conducted a survey of 95 respondents of community farmers in the agricultural landscape in Sukapura and Resmi Tingal Village using questionnaire guidelines and direct interviews to gather information. There was a significant decrease in plant diversity in some plot agroforests, which, in the previous study, was dominant to be reduced even to local extinctions. The results also show that the farmer poverty index according to BPS criteria is 12.63% of respondents who are below the poverty line. Our results imply that preserving mixed-garden (talun) patches in a landscape dominated by cash-crop gardens is one of the strategies that could conserve landscape biodiversity and increasingly a sustainable livelihood. Keywords: agriculture commercialization, agroforestry, land use change, poverty index, rural development